Generalised Choquet Integral Algorithm for Subcontractor Selection in the Textile Industry - A Case Study for Turkey - (:unkn) unknown (INST CHEMICAL FIBRES, 2013)
Turkish textile firms work under a heavily competitive atmosphere in terms of prices due to globalisation. Firms have to take into consideration several criteria in order to survive the global market conditions and to maintain profitability. Contractor companies have to select the optimal subcontractor in order to meet these criteria and in business. Therefore the decision to choose subcontractors is of great importance for the success of enterprises. In solving the problem of subcontractor selection, multiple criteria should be considered, for which multi-criteria decision-making methods are used. This paper presents a case study which regards the selection of the optimal subcontractor for a Turkish textile firm. In order to solve the selection problem generalized Choquet integral methodology was used based on a hierarchical decision model. In the conclusion section of the study, optimal subcontractor selection results are presented.
Keywords: subcontractor selection; Turkish textile industry; generalised Choquet integral methodology; CONTRACTOR